1990
DOI: 10.1111/j.1365-3083.1990.tb02746.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Murine Liver‐Derived Inhibitory Protein

Abstract: Murine liver-derived inhibitory protein (LIP) capable of inhibiting human lymphocyte proliferation was highly purified from liver extract. Its molecular weight determined by gel filtration and SDS-PAGE was 105,000 and 38,400 respectively. LIP moved electrophoretically at the gamma-globulin region. Its activity in inhibiting lymphocyte proliferation was temperature-stable up to 60 degrees C, and pH-stable between 4 and 11. It was not cytotoxic to lymphocytes as shown in 51Cr-release experiments. The purified LI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The gel was electroblotted onto a polyvinylidene difluoride membrane according to the procedure of Matsudaira (23). The membrane was rinsed in distilled water (10 min), stainedwith 0.1% Coomassie blue (10 min) and destained with 50% methanoltlO% acetic acid (10 min). After being rinsed in distilled water, the membrane was air dried.…”
Section: Fast Protein Liquid Chronaatography-chromato@wingmentioning
confidence: 99%
See 2 more Smart Citations
“…The gel was electroblotted onto a polyvinylidene difluoride membrane according to the procedure of Matsudaira (23). The membrane was rinsed in distilled water (10 min), stainedwith 0.1% Coomassie blue (10 min) and destained with 50% methanoltlO% acetic acid (10 min). After being rinsed in distilled water, the membrane was air dried.…”
Section: Fast Protein Liquid Chronaatography-chromato@wingmentioning
confidence: 99%
“…Mouse liver arginase has M, of 38,400 and 105,000 under denaturing and nondenaturing conditions, respectively, and may exist as a trimer (10). To rule out the possibility that arginase could not be measured with the functional enzyme assay because of dissociation into subunits during sample processing, ELISA was used to quantitate arginase protein.…”
Section: Inhibitory Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…(3,4) Although arginase activity is most abundant in mammalian liver, (5) it is also found in nonhepatic tissues, such as red blood cells, (6) lactating mammary glands, (7) and the kidney. (8) In addition to its involvement in ammonia detoxification via the urea cycle, arginase plays a role in other processes, such as macrophagemediated cytotoxicity due to arginase release (9) and inhibition of lymphocyte proliferation in vitro, (10,11) and shows high activity in growing tissues, proliferating lymphocytes (12) and tumors. (13) In addition, recent studies have suggested that arginase may act as a modulator of the immune response, (14) because an inhibitor of the mixed-lymphocyte reaction, purified from rat liver, has high N-terminal sequence homology with rat liver arginase and also displays arginase activity.…”
Section: Introductionmentioning
confidence: 99%
“…(13) In addition, recent studies have suggested that arginase may act as a modulator of the immune response, (14) because an inhibitor of the mixed-lymphocyte reaction, purified from rat liver, has high N-terminal sequence homology with rat liver arginase and also displays arginase activity. (10) Although a polyclonal ELISA (15) or an enzyme activity assay (4,11,12) is currently used to measure plasma arginase levels, a more sensitive method is required to detect lower levels in plasma and culture supernatants. The hybridoma technique, developed by Köhler and Milstein, (16,17) allows the production of monoclonal antibodies (MAbs) that specifically recognize a particular antigen determinant.…”
Section: Introductionmentioning
confidence: 99%